Financial Information System in Increasing Organizational Stability (Case Study on Ar-Ruhama Organized Foundation) - Puji Karyono, Wahiyo; Yulisa Geni, Bias (SAINTEKBU, 2023)
The current development of Information Technology has increased the need for effective and efficient financial transaction recording. Yatim Piatu Ar-Ruhama Foundation needs to have a financial information system that can assist in managing and reporting their finances. This research aims to develop a Financial Information System to enhance the organization's stability of Ar-Ruhama Foundation. The research methodology includes software requirement analysis, such as budget management, financial transaction recording, financial reporting, donation management, and data security. This Financial Information System will enable the foundation to record financial transactions, manage budgets, generate accurate financial reports, and handle received donations. The findings of this research are expected to help Ar-Ruhama Foundation in preparing transparent and accurate financial reports and improving organizational stability through efficient financial management.